Longitudinal cognitive decline in the AIBL cohort: The role of APOE ε4 status. (August 2015) - Albrecht, Matthew A.; Szoeke, Cassandra; Maruff, Paul; Savage, Greg; Lautenschlager, Nicola T.; Ellis, Kathryn A.; Taddei, Kevin; Martins, Ralph; Masters, Colin L.; Ames, David; Foster, Jonathan K.
Abstract: The ε4 polymorphism of the APOE gene confers a substantially increased risk of developing Alzheimer's disease. However, the influence of the ε4 allele on age-related cognitive functioning is more contentious. Previously, we demonstrated relatively little evidence for a role of the ε4 allele on baseline cognitive performance in older adults in the Australian Imaging, Biomarkers and Lifestyle (AIBL) Study of Ageing (Foster et al., 2013 ). We here investigated whether the APOE ε4 allele influenced cognitive status over time when the AIBL cohort was studied longitudinally over a 3-year period. The AIBL neuropsychological test battery was administered at baseline, after 18 months and again after 36 months. Participants comprised 764 Healthy Controls and 131 Mild Cognitively Impaired individuals enroled in the AIBL Study of Ageing. We compared individuals within each group with and without an ε4 allele. Healthy Controls with an ε4 allele manifested a modest acceleration in cognitive decline over 36 months on measures of verbal episodic memory. By contrast, Mild Cognitively Impaired individuals with an ε4 allele showed increased cognitive decline across a range of cognitive tasks, putatively reflecting early cognitive signs of Alzheimer's disease. Given the long prodromal period that has been noted in late onset Alzheimer's disease, we suggest that these findings are consistent with a prodromal account rather than a phenotypic account of ε4-related cognitive ageing. Highlights: Longitudinal investigation into the Alzheimer's risk allele APOE ε4 on cognitive status. 764 Healthy Controls and 131 Mild Cognitively Impaired were assessed over 3 years. Possession of the ε4 allele increased verbal episodic memory decline in Healthy Controls. In Mild Cognitively Impaired, the ε4 allele was associated with general cognitive decline.